The Complete Codes and Statutes of the State of Montana 1084, § 759 (1895) - (:unkn) unknown (My University, 1895)
Pt. 1, tit. 11, § 759: Every person who brings into this state an armed person or armed body of men for the preservation of the peace or the suppression of domestic violence, except at the solicitation and by the permission of the legislative assembly or of the governor, is punishable by imprisonment in the state prison not exceeding ten years and by a fine not exceeding ten thousand dollars.
Keywords: MILITIAS